Implementasi Pendidikan Agama Islam Dalam Meningkatkan Pemahaman Agama - Ismi Izzatul Shoumi (Jurnal Dirosah Islamiyah, 2023)
Islamic religious education is very much needed by the Islamic community today to add insight in understanding religion, because in fact there are still many people who lack understanding of religion, lack of understanding of religion will greatly affect a person in carrying out daily worship and activities related to religion. In the context of fostering religious education in the community, efforts can be made through regular recitations, one of which is found at the Al-Muchlisin taklim assembly. With this taklim assembly, it will help the community in increasing religious understanding and can foster society towards an Islamic society in accordance with the teachings of Islam. So it is deemed necessary for researchers to conduct a research in the form of a thesis with the title "Implementation of Islamic Religious Education in Improving Religious Understanding of Mothers of the Al-Muchlisin Taklim Council of BTN Purnasari Leuwiliang, with the aim of knowing how the Implementation of Islamic Religious Education in Improving Mothers' Religious Understanding" Al-Muchlisin Taklim Council BTN Purnasari Leuwiliang. This study uses a qualitative descriptive method with a field study approach (field research). Data collection techniques through observation, documentation and interviews. This research method uses the triangulation method of data sources by conducting interviews with the main subjects, namely the teachers, administrators and congregation of the women of the Al-Muchlisin taklim assembly. The results of this study show that the implementation of Islamic religious education can improve the religious understanding of the women of the Al-Muchlisin taklim assembly seen from their mastery of the material obtained in terms of faith, ubudiyah to Allah and good morals that are applied in everyday life. Keywords: Implementation, Islamic Religious Education, Religious Understanding